Contribution of collapse perforation to the production of loose sand in the wellbore - Samsuri, Ariffin (1992)
This paper present the results of a laboratory study of the loose sand produced from the collapse perforation. Sections of a perforated wellbore were generated and expose to various rock mechanical stresses and conclusions were drawn with respect to the produced loose sand during loading process, up to failure of the perforated structure. The results show that the perforation may fail during the creation process and the oversized 500 microns loose sand were produced or subsequent production life, depending on the perforation length, shot density, phasing angle and pattern, and rock properties. In general, stable perforated wellbore can minimize the loose sand production in the wellbore, therefore minimizing the sand production problems.